Evaluation of a new patient safety educational programme to reduce adverse events by encouraging staff to speak up: application of the trigger tool methodology - Kaoru Nakatani; Etsuko Nakagami-Yamaguchi; Tetsuro Nishimura; Yasumitsu Mizobata; Naohiro Hagawa; Atsushi Tokuwame; Shoichi Ehara (BMJ Open Quality, 2024)
Background Poor communication contributes to adverse events (AEs). In our hospital, following an experience of a fatal incident in 2014, we developed an educational programme aimed at improving communication for better teamwork that led to a reduction in AEs.Methods We developed and implemented an intervention bundle comprising external investigation committee reviews, the establishment of a working group (WG), standards and emergency response guidelines, as well as educational programmes and tools. To determine the effectiveness of the educational programmes, we measured communication abilities among doctors and nurses by administering psychological scales focused on their confidence in speaking up. Furthermore, we applied the trigger tool methodology in a retrospective study to determine if our interventions had reduced AEs.Results The nurses’ scores for ‘perceived barriers to speaking up’ and ‘negative attitude toward voicing opinions in the healthcare team’ decreased significantly after the training from 3.20 to 3.00 and from 2.47 to 2.29 points, respectively. The junior doctors’ scores for the same items also decreased significantly after the training from 3.34 to 2.51 and from 2.42 to 2.11 points, respectively. The number of AEs was 32.1 (median) before the WG, 39.9 (median) before the general training, 22.2 (median) after the general training and 18.4 (median) after implementing the leadership educational programmes. During the intervention period the hospital’s incident reports per employee kept increasing.Conclusion Our new educational programmes improved junior doctors and nurses’ perceptions of speaking up. We speculated that our intervention may have improved staff communication, which in turn may have led to a reduction in AEs and a sustained increase in incident reports per employee.